Efektivitas Penggunaan Video Pembelajaran terhadap Peningkatan Hasil Belajar IPA Siswa SD: Literature Review - Nabila, Aulia; Melati, Riana Puspa; Pransiska, Septina Dea; Darwanto (RUKASI: Jurnal Ilmiah Perkembangan Pendidikan dan Pembelajaran, 2025)
The purpose of this research is to explore how the role of animated video media can contribute to improving the quality of the learning process, especially in Natural Science (IPA) subjects at the elementary school level. Special emphasis is given to the effectiveness of this media in supporting students' understanding of scientific concepts. The learning process, which is still largely carried out using conventional methods, is considered less engaging and less motivating for students, so innovation is needed through the utilization of technology in accordance with the demands of the Society 5.0 Era. This research was conducted using a literature review approach, which involves gathering information from various reference sources such as books, scientific journals, articles, and reports of previous research findings. This step is taken to obtain a theoretical foundation and data relevant to the topic of study. The analysis results show that animated video media, which falls under the category of audiovisual media, is able to present abstract material in a more concrete way, attract attention, and improve students' understanding and interest in learning. Animated videos are effective in explaining difficult concepts, such as the human digestive process, because they provide visualization and audio simultaneously. Various studies also reveal that the use of technology-based interactive media can address the problems of Natural Science learning at the elementary school level in an enjoyable way, so that students get a pleasant learning experience, increase motivation, and encourage the development of critical thinking skills.